Effect of postoperative systemic prednisolone on short-term and long-term outcomes in chronic rhinosinusitis with nasal polyps: A multi-centered randomized clinical trial - Mueller, Sarina K.; Wendler, Olaf; Mayr, Susanne; Traxdorf, Maximilian; Hosemann, Werner; Olze, Heidi; Steinhart, Helmut; Wiegand, Susanne; Teymoortash, Afshin; Kuehnel, Thomas; Hackenberg, Stephan; Hummel, Thomas; et al. (Frontiers in Immunology, 2023)
The objective of this study was to determine whether postoperative additive systemic steroid administration in chronic rhinosinusitis with nasal polyps (CRSwNP) impacted selected endoscopic, subjective and objective outcome measures. This was a prospective, randomized, double-blind, placebo-controlled, noninferiority multicenter trial of n=106 patients with CRSwNP. All patients underwent primary functional endoscopic sinus surgery (FESS) followed by topical nasal steroids. Patients were randomized to a systemic steroid or placebo for 1 month. Patients were followed up for 2 years over 9 time points. The primary outcome measures were the differences between groups with respect to the nasal polyp score (NPS) and sinonasal quality of life (SNQoL). Secondary outcome measures included interactions with respect to the Lund-Kennedy score (LKS), sinonasal symptoms, general quality of life (GQoL), 16-item odor identification test scores, recurrence rates, need for revision surgery and mucus biomarker levels. 106 patients were randomized to either the placebo or the systemic steroid group (n=53 per group). Postoperative systemic steroids were not superior to placebo with respect to all primary (p= 0.077) and secondary outcome measures (p>0.05 for all). Reported adverse events were similar between the two groups. In conclusion, the addition of postoperative systemic steroids after primary FESS did not confer a benefit over topical steroid nasal spray alone with respect to NPS, SNQOL, LKS, GQOL, sinonasal symptoms, smell scores, recurrence rates, the need for revision surgery or biomarkers over a short-term follow-up of up to 9 months and a long-term follow-up of up to 24 months in CRSwNP patients. Functional endoscopic surgery did, however, show a strong effect on all outcome measures, which remained relatively stable up to the endpoint at 2 years.